Sex differences in blood pressure response to continuous and II infusion: Involvement of sex chromosome complement and hormonal effects - Dadam, Florencia (2017)
Fil: Dadam, Florencia. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigación Médica Mercedes y Martín Ferreyra; Argentina.